Micropropagation of somatic embryo derived plants of Hevea brasiliensis - Sushamakumari S; Sobha S (National Symposium on Prospects and Potentials of Plant Biotechnology in India in the 21st Century and 23rd Annual Meeting of PTCA (India) 18th - 21st October, 2000 : Abstracts and Souvenir)
A plant regeneration pathway via somatic embryogenesis from immature inflorescene of Hevea brasiliensis has been developed. In this system an average embryo induction frequency of around 50;could be achieved. However, conversion of the somatic embryos into full plantlets has got several constraints like the low percentage of embryo maturation and the occurrence of abnormal embryos incapable of regenerating into plants. Hence alternative techniques for multiplication of already obtained normal embryos and somatic plants have been attempted. Two systems could be developed a) multiple shoot formation from somatic embryos b) multiplication of somatic plants through microcuttings. In the former system multiple shoots were induced on normal cotyledonary somatic embryos. Among different cytokinins tried, BA and TDZ were found to be effective in inducing multiple shoots from the germinating somatic embryos. High concentration of BA (22.0mM) was required whereas lower levels of TDZ (1.0-2.0mM) were sufficient for multiple shoot induction. However, microshoots induced in the presence of BA showed better elongation and high rooting percentage than those induced by TDZ. Elongated shoots got rooted in hormone-free medium. An average of 3 microshoots per explant could be induced by this system. In the second method, actively growing somatic plants under in vitro conditions were cut into segments containing at least one node and individual segments were cultured in elongation medium containing BA (4.4mM). The elongated shoots were transferred to rooting medium in which BA was replaced with IBA (5.0mM). Around 80-90;rooting was observed. Even though the process of segmentation and elongation could be repeated over and again, after 2-3 cycles growth and vigour of the microcuttings was found to be declining. An average multiplication rate of 10 per somatic plant could be achieved through this technique.
Keywords: Hevea brasiliensis; Microcuttings; Micropropagation; Multiple shoot formation; Somatic embryo